2022
DOI: 10.1155/2022/9714252
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Exercise Rehabilitation in Patients with Atrial Fibrillation after Radiofrequency Ablation: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background and Aims. Radiofrequency ablation is a commonly used treatment for paroxysmal atrial fibrillation (AF), but postoperative rehabilitation exercises are needed to reverse left ventricular structural and functional abnormalities. This meta-analysis aimed to evaluate the intervention effect of exercise training in patients with AF after radiofrequency ablation. Methods. A systematic literature search was conducted to identify articles in PubMed, MEDLINE, EMBASE, and the Cochrane Library from January 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(45 reference statements)
2
4
1
Order By: Relevance
“…As for the effect of CR on patient cardiac function after RCFA, CR may not affect LVEF. This result was contrary to a previous systematic review [ 23 ], which revealed a small effect, with an MD of 0.09 (95%CI 0.01, 0.17). While other reports have indicated improved LVEF in patients with heart failure following CR, the studies included in our analysis [ 36 , 38 , 42 ] reported normal baseline LVEF values.…”
Section: Reviewcontrasting
confidence: 99%
See 1 more Smart Citation
“…As for the effect of CR on patient cardiac function after RCFA, CR may not affect LVEF. This result was contrary to a previous systematic review [ 23 ], which revealed a small effect, with an MD of 0.09 (95%CI 0.01, 0.17). While other reports have indicated improved LVEF in patients with heart failure following CR, the studies included in our analysis [ 36 , 38 , 42 ] reported normal baseline LVEF values.…”
Section: Reviewcontrasting
confidence: 99%
“…However, the results are uncertain because fewer than three studies were included in that review, and exercise intensity was not standardized. Another systematic review also examined CR's effect on patients after RFCA [ 23 ], but safety was not discussed, and the included papers found non-directiveness. Thus, this systematic review aimed to examine the AF recurrence associated with moderate exercise-based CR in patients with AF after RFCA, as well as with exercise function and cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…Forest plot shows the ES of physical exercise on peak vo2 in AF patients. Compared with the previous analysis (8,9), our study included more types of patients with AF, such as patients with AF after radiofrequency ablation and patients with heart failure with AF (10,16,18,19,23). The reason why we do so is mainly to consider that the clinical condition of some AF patients is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer types of AF patients were included in the study (8,9), and the effect of exercise on cardiac function in patients with AF is unclear despite previous meta-analyses in this area. After searching relevant experiments, we found some controversy about whether exercise can improve the LVEF in patients with atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the latest report from the European Society of Cardiology on AF management highlights the importance of encouraging patients with AF to engage in moderate-intensity exercise and maintain physical activity levels to reduce the risk of AF [8]. Data from systematic reviews and meta-analyses have reported substantial improvements in cardiovascular capacity and quality of life for individuals with AF who underwent cardiac rehabilitation [13][14][15][16]. However, the research on exercise training for AF patients has employed diverse protocols, underscoring the lack of clear consensus regarding the exact exercise recommendations for individuals with AF, in contrast to other cardiovascular diagnosis.…”
Section: Introductionmentioning
confidence: 99%